Synthesis and cell-free cloning of DNA libraries using programmable microfluidics - Ben Yehezkel, Tuval; Rival, Arnaud; Raz, Ofir; Cohen, Rafael; Marx, Zipora; Cámara, Miguel; Dubern, Jean-Frédéric; Koch, Birgit; Heeb, Stephan; Krasnogor, Natalio; Delattre, Cyril; Shapiro, Ehud (Oxford University Press, 2016)
Microfluidics may revolutionize our ability to write synthetic DNA by addressing several fundamental limitations associated with generating novel genetic constructs. Here we report the first de novo synthesis and cell-free cloning of custom DNA libraries in sub-microliter reaction droplets using programmable digital microfluidics. Specifically, we developed Programmable Order Polymerization (POP), Microfluidic Combinatorial Assembly of DNA (M-CAD) and Microfluidic In-vitro Cloning (MIC) and applied them to de novo synthesis, combinatorial assembly and cellfree cloning of genes, respectively. Proof-of-concept for these methods was demonstrated by programming an autonomous microfluidic system to construct and clone libraries of yeast ribosome binding sites and bacterial Azurine, which were then retrieved in individual droplets and validated. The ability to rapidly and robustly generate designer DNA molecules in an autonomous manner should have wide application in biological research and development.